The Effect of Progressive Relaxation Techniques on Anxiety of Bua Raga Fc Sepak Takraw Athletes: Before and During the Match - Irham, Irham; Hidayat, Rachmat; Anuar, Arman Bin; Riswanto, A Heri; Tunru, Andi Alif (Department of Physical Education, Sport, Health and Recreation, 2024)
The aim of this research is to determine the effect of progressive relaxation techniques on the anxiety of Bua Raga Fc sepak takraw athletes. This research used Pretest-Posttest Design; giving a pretest before treatment, and a posttest afterward in the experimental group. The population in this study is all 15 Bua Raga Fc sepak takraw athletes. The sample is 15 Bua Raga Fc sepak takraw athletes. The sampling technique used is saturated sampling where all members of the population are sampled in this research. The data collection technique uses a questionnaire or questionnaire which uses an anxiety test instrument by (Tangkudung, 2018). Research data was analyzed descriptively, testing requirements; data normality and homogeneity tests, paired sample t-test. according to the significant levelα= 0.05. The results of the study show that there is a significant influence of progressive relaxation techniques on the anxiety of Bua Raga Fc sepak takraw athletes, with a t = calculated value of 17.905, this value is bigger than t = table 2.131 or t= count of 17.905 > t=table 2.131 and the result is sig. (2-tailed) which is 0.000 < 0.05. The average pretest anxiety score is 51.27 and the average posttest anxiety score is 40.67, there is a difference between groups of 10.6. The conclusion is that there is a decrease in athlete anxiety after being given progressive relaxation techniques. Thus, the progressive muscle relaxation technique is effective in reducing anxiety in Bua Raga Fc sepak takraw athletes.